2004
DOI: 10.1021/es049128x
|View full text |Cite
|
Sign up to set email alerts
|

Modern and Historic Atmospheric Mercury Fluxes in Northern Alaska:  Global Sources and Arctic Depletion

Abstract: We reconstruct from lake-sediment archives atmospheric Hg deposition to Arctic Alaska over the last several centuries and constrain a contemporary lake/watershed mass-balance with real-time measurement of Hg fluxes in rainfall, runoff, and evasion. Results indicate that (a) anthropogenic Hg impact in the Arctic is of similar magnitude to that at temperate latitudes; (b) whole-lake Hg sedimentation determined from 55 210Pb-dated cores from the five small lakes demonstrates a 3-fold increase in atmospheric Hg de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
167
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(190 citation statements)
references
References 47 publications
18
167
0
Order By: Relevance
“…Three reasons may explain the large difference between lake and tundra snowpack Hg loads: (1) the lake did not accumulate the snowpack on open water prior to the lake surface freezing in the early fall (Sturm and Liston, 2003); (2) low surface roughness over the lake likely prevent settling of snowfall and facilitate remobilization of snow by wind transport (Essery et al, 1999;Essery and Pomeroy, 2004); and (3) the lake ice is warmer than the tundra soil resulting in higher sublimation over the lake. The implication of the latter process is a reduction of direct atmospheric deposition over Arctic lakes and is consistent with studies that estimated that annual Hg contribution to Arctic lakes via direct wet deposition is small, generally less than 20 % of total deposition (Fitzgerald et al, 2005(Fitzgerald et al, , 2014. Spatial redistribution of snow across the tundra landscape further implies that both wet deposition and snow accumulation rates are variable, leading to spatial heterogeneity of snowmelt Hg inputs.…”
Section: Snowbound Mercury In the Interior Arctic Snowpack 331 Spatsupporting
confidence: 86%
See 1 more Smart Citation
“…Three reasons may explain the large difference between lake and tundra snowpack Hg loads: (1) the lake did not accumulate the snowpack on open water prior to the lake surface freezing in the early fall (Sturm and Liston, 2003); (2) low surface roughness over the lake likely prevent settling of snowfall and facilitate remobilization of snow by wind transport (Essery et al, 1999;Essery and Pomeroy, 2004); and (3) the lake ice is warmer than the tundra soil resulting in higher sublimation over the lake. The implication of the latter process is a reduction of direct atmospheric deposition over Arctic lakes and is consistent with studies that estimated that annual Hg contribution to Arctic lakes via direct wet deposition is small, generally less than 20 % of total deposition (Fitzgerald et al, 2005(Fitzgerald et al, , 2014. Spatial redistribution of snow across the tundra landscape further implies that both wet deposition and snow accumulation rates are variable, leading to spatial heterogeneity of snowmelt Hg inputs.…”
Section: Snowbound Mercury In the Interior Arctic Snowpack 331 Spatsupporting
confidence: 86%
“…In the Arctic, modern atmospheric Hg deposition has increased about 3-fold from preindustrialized background levels (Fitzgerald et al, 2005), similar to increases observed in temperate locations, although other studies suggest much stronger increases (e.g., Enrico et al, 2017). The increase in Hg loading has led to vulnerability of polar ecosystems to Hg contamination due to detrimental impacts to wildlife and humans, in particular through biomagnification processes across trophic levels (Atwell et al, 1998).…”
Section: Introductionmentioning
confidence: 62%
“…In freshwater, however, significant increases in THg fluxes to sediments during the 20th century indicate that deposited atmospheric Hg has had an effect on Hg levels in lake sediments and, by extension, on freshwater Hg budgets in the Arctic. [21][22][23] Results from a recent study of marine sediments from Hudson Bay indicate THg concentrations increased during the 20th century. [24] Deposited Hg either enters aquatic environments (marine systems, melt ponds on sea ice, lakes or rivers) or remains in soils or the multi-year snow and ice found on glaciers and ice sheets (Fig.…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 99%
“…[22] Thus the integration of this atmospheric Hg into ecosystem soils and vegetation may be limited. Erosion of thawed soils during summer, a process that seems to be accelerated by climate change, provides an important source of inorganic Hg to lakes in Alaska [21] and possibly elsewhere in the Arctic. [48,49] Soil loadings of Hg to Alaskan lakes were found to be associated primarily with silt [21] and were greater in lakes with higher watershed/lake area ratios.…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 99%
“…Levels of chemicals are particularly elevated in coastal ecosystems because of river influxes, runoff, point-source pollution, and atmospheric transport and deposition (Furness and Rainbow 1990;Burger and Gochfeld 2002). Many chemicals, such as mercury, are transported all over the world, including to relatively isolated lakes and oceanic environments (Fitzgerald 1989;Houghton et al 1992;Fitzgerald et al 2005;Hammerschmidt et al 2006). Atmospheric deposition is of particular interest for mercury because the USA and other industrialized nations are poorly regulating emissions (Evers et al 2005).…”
Section: Introductionmentioning
confidence: 99%